A hitchhiker’s guide to an ISS experiment in under 9 months - Andrei James Nadir (Nature Portfolio, 2017)
Abstract The International Space Station National Laboratory gives students a platform to conduct space-flight science experiments. To successfully take advantage of this opportunity, students and their mentors must have an understanding of how to develop and then conduct a science project on international space station within a school year. Many factors influence the speed in which a project progresses. The first step is to develop a science plan, including defining a hypothesis, developing science objectives, and defining a concept of operation for conducting the flight experiment. The next step is to translate the plan into well-defined requirements for payload development. The last step is a rapid development process. Included in this step is identifying problems early and negotiating appropriate trade-offs between science and implementation complexity. Organizing the team and keeping players motivated is an equally important task, as is employing the right mentors. The project team must understand the flight experiment infrastructure, which includes the international space station environment, payload resource requirements and available components, fail-safe operations, system logs, and payload data. Without this understanding, project development can be impacted, resulting in schedule delays, added costs, undiagnosed problems, and data misinterpretation. The information and processes for conducting low-cost, rapidly developed student-based international space station experiments are presented, including insight into the system operations, the development environment, effective team organization, and data analysis. The details are based on the Valley Christian Schools (VCS, San Jose, CA) fluidic density experiment and penicillin experiment, which were developed by 13- and 14-year-old students and flown on ISS.